2014
DOI: 10.1016/j.ejvs.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-analysis of Direct Versus Indirect Angiosomal Revascularisation of Infrapopliteal Arteries

Abstract: DR of the tibial vessels appears to result in improved wound healing and limb salvage rates compared with IR, with no effect on mortality or reintervention rates. However, the quality of evidence on which these conclusions are based on is low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(48 citation statements)
references
References 40 publications
2
45
1
Order By: Relevance
“…245257 Meta-analyses of these studies found improved wound healing and limb salvage with angiosome-guided therapy but cautioned that the quality of the evidence was low. 258,259 Although the angiosome concept is theoretically satisfying, randomized data comparing the establishment of in-line flow versus angiosome-guided therapy have yet to be published. Furthermore, there is no evidence yet to demonstrate the potential benefit of treating additional infrapopliteal arteries once in-line flow has been established in one artery, regardless of angiosome.…”
Section: Management Of Cli: Recommendationsmentioning
confidence: 99%
“…245257 Meta-analyses of these studies found improved wound healing and limb salvage with angiosome-guided therapy but cautioned that the quality of the evidence was low. 258,259 Although the angiosome concept is theoretically satisfying, randomized data comparing the establishment of in-line flow versus angiosome-guided therapy have yet to be published. Furthermore, there is no evidence yet to demonstrate the potential benefit of treating additional infrapopliteal arteries once in-line flow has been established in one artery, regardless of angiosome.…”
Section: Management Of Cli: Recommendationsmentioning
confidence: 99%
“…A recent retrospective review suggests that revascularization efforts (surgical or endovascular) are more likely to be successful when targeted to the vessel supplying the affected angiosome in the foot. 71 Future trials of angiogenic/arteriogenic therapies for CLI will likely incorporate this concept.…”
Section: Summary Of Angiogenic Therapies For Padmentioning
confidence: 99%
“…For heel PUs, direct revascularisation is achieved by reperfusing the peroneal and PTAs. Recent evidence has suggested that direct revascularisation results in improved wound healing and lower rates of amputation when compared with indirect revascularisation (69). However, indirect revascularisation may be adequate when sufficient collaterals are present (70), which explains why heel PUs can heal by reperfusing the anterior tibial artery.…”
Section: Revascularisationmentioning
confidence: 99%